Knowledge review on poverty and rural development in Nigeria - Omonona, Bolarin T. (International Food Policy Research Institute, 2009)
The Nigerian situation presents a paradox because the country is rich but the people are poor, with the poverty experienced by Nigerians being pervasive, multifaceted and chronic, affecting the lives of a large proportion of the populace. On the average, the incidence of poverty in Nigeria has been on the increase since 1980. NBS (2007) reveals that the incidence of poverty increased sharply both between 1980 and 1985 (from 28.1 percent to 46.3 percent) and between 1992 and 1996 (from 42.7 percent to 65.6 percent) though there were declines between 1985 and 1992 (from 46.3 percent to 42.7 percent) and between 1996 and 2004 (from 65.6 percent to 54.4 percent). And despite the reduction in poverty incidence between the two periods, the absolute number of the poor in Nigeria has been on the rise.